DESENVOLVIMENTO DE COMPRIMIDOS CONTENDO DISPERSÕES SÓLIDAS AMORFAS DE NORFLOXACINO COMO UM SISTEMA SUPERSATURADO DE LIBERAÇÃO DE FÁRMACO - Zela, Sarah Jáuregui (2020)
Norfloxacin (NFX) is one of the most commonly used medication in urinary tract infections, affecting around 150 million people worldwide each year. However, NFX has low solubility and dissolution rate and, consequently, reduced oral bioavailability, since only NFX exhibits a low 40% of the oral dose taken in is absorbed. The objective of this research was to develop the pharmaceutical form of tablet of norfloxacin solid dispersions, aiming to increase the solubility of the final product. Solid dispersions were obtained by spray drying using the 1:1 drug: polymer ratio (NFX: HPMC E6). Tablets were obtained by dry granulation in a URM-10 (Usirom) compressor with a fixed amount of solid Norfloxacin dispersions. A study of the compatibility of the physical mixtures of the active ingredient with the excipients as well as the technological characteristics of the tablets (density, appearance, dimensions, average weight, hardness, friability, disintegration, dosage) were evaluated using DSC and TG. The research of the dissolution was also performed under conditions of supersaturation in a simulated biologically relevant atmosphere as well as sober intestinal fluid (FaSSIF). The collected samples were quantified by the chromatographic method in a high performance liquid chromatograph (Shimadzu), using Luna® column, flow rate 1.0 mL min-1, injection volume 20 μL, oven temperature 40° C, acetonitrile mobile phase: 0.01M phosphate buffer pH 3.5 (at 16:74, v/v proportions). The developed formulations NFX DS F3 and NFX DS F4 demonstrated an increase of 154.44% and 164.31% over the reference NFX. This increase in NFX dissolution rate through the obtained tablets may reflect in greater bioavailability, since the medication becomes more available for absorption. The stability studies determined that the formulations of NFX DS F3 and F4 remained stable when exposed for 90 days at 40° C and 4° C, demonstrating the need for impermeable packaging for the protection and maintenance of the amorphous product.